Ion Channels in Hematopoietic and Mesenchymal Stem Cells - Serena Pillozzi; Andrea Becchetti (Hindawi Limited, 2012)
Hematopoietic stem cells (HSCs) reside in bone marrow niches and give rise to hematopoietic precursor cells (HPCs). These have more restricted lineage potential and eventually differentiate into specific blood cell types. Bone marrow also contains mesenchymal stromal cells (MSCs), which present multilineage differentiation potential toward mesodermal cell types. In bone marrow niches, stem cell interaction with the extracellular matrix is mediated by integrin receptors. Ion channels regulate cell proliferation and differentiation by controlling intracellular Ca2+, cell volume, release of growth factors, and so forth. Although little evidence is available about the ion channel roles in true HSCs, increasing information is available about HPCs and MSCs, which present a complex pattern of K+ channel expression. K+ channels cooperate with Ca2+ and Cl− channels in regulating calcium entry and cell volume during mitosis. Other K+ channels modulate the integrin-dependent interaction between leukemic progenitor cells and the niche stroma. These channels can also regulate leukemia cell interaction with MSCs, which also involves integrin receptors and affects the MSC-mediated protection from chemotherapy. Ligand-gated channels are also implicated in these processes. Nicotinic acetylcholine receptors regulate cell proliferation and migration in HSCs and MSCs and may be implicated in the harmful effects of smoking.